Selected socio-economic impacts of Lumot Lake on the municipality of Cavinti some policy recommendations - Miranda, Praksis A (2005)
This exploratory study is a pioneering research on Lumot Lake. It differs from other lake impact studies by taking the perspective of the Cavitenos. IT will determine if the local folk of Cavinti and the municipality as a whole are reapinf most of the benefits derived from Lumot lake...